2014
DOI: 10.1371/journal.pbio.1001979
|View full text |Cite
|
Sign up to set email alerts
|

Cell Fate Regulation Governed by a Repurposed Bacterial Histidine Kinase

Abstract: The pathway that regulates asymmetric cell division in Caulobacter involves a signaling kinase whose catalytic output domain has been repurposed as an input sensor of the phosphorylation state of the response regulator – a reversal of the conventional direction of information flow; this allows wiring of simple linear signaling pathways into complex eukaryote-like networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 66 publications
(115 reference statements)
8
77
0
Order By: Relevance
“…S5(A)] indicate that these interaction sites are flexible. This is consistent with the known behavior of other histidine kinases . Interestingly, contact with the RR protein also appears to stabilize an additional segment of the Af GcHK kinase domain, which includes helix H12, loop L16 and part of β‐strand B4.…”
Section: Discussionsupporting
confidence: 83%
“…S5(A)] indicate that these interaction sites are flexible. This is consistent with the known behavior of other histidine kinases . Interestingly, contact with the RR protein also appears to stabilize an additional segment of the Af GcHK kinase domain, which includes helix H12, loop L16 and part of β‐strand B4.…”
Section: Discussionsupporting
confidence: 83%
“…In Caulobacter cells protein complexes of different composition are assembled at opposite cell poles where they control cell-type-specific functions, including signaling protein-mediated differential expression of the genome after cell compartmentalization and MipZ-directed positioning of the divisome (12,13,15,(28)(29)(30)(31). During the swarmer to stalked cell transition, the protein complex of the formerly flagellated pole is replaced by the proteins required at a stalked pole protein complex.…”
Section: Spmx Is Synthesized In the Swarmer Cell For Immediate Localimentioning
confidence: 99%
“…The expression of cell cycle-controlled mRNAs largely correlates with the times they are required for the functional modules that implement progression of the cell cycle (8). The transcriptional activity of most of the Caulobacter cell cycle-regulated promoters is controlled by a genetic circuit comprised of four transcriptional master regulators, a DNA methyltransferase (2), and a dynamic set of polar-localized phospho-signaling proteins that control asymmetric cell division (12)(13)(14)(15). Because regulation of translation has an immediate impact on protein production, a major cellular energy drain, tight regulation of translation is essential for rapid cell adaptation to changing circumstances.…”
mentioning
confidence: 99%
“…[1,3,13,14] Unlike many modular domainsc onnected by flexible linkers, histidine kinases appear to rely on rigidh elicall inkerst hat transmiti nformation between domains. [6,[16][17][18] Modeling based on aminoa cid insertion experiments now suggest that the relative position of these helices in the VirA dimer control kinase activity through combined piston and twisting motions. [1,9,19] Additional experimentsh ave further confirmed that the positioning of the anchoring TM2 trans-membrane helix is critical for sugar input into the Ldomain.…”
Section: Introductionmentioning
confidence: 99%